A review of Human Biomonitoring studies of trace elements in Pakistan - Waseem, Amir; Arshad, Jahanzaib (Chemosphere (Oxford), 2016)
Human biomonitoring (HBM) measures the concentration levels of substances or their metabolites in human body fluids and tissues. HBM of dose and biochemical effect monitoring is an effective way of measuring human exposure to chemical substances. Many countries have conducted HBM studies to develop a data base for many chemicals including trace metals of health concern for their risk assessment and risk management. However, in Pakistan, HBM program on large scale for general population does not exist at present or in the past has been reported. Various individual HBM studies have been reported on the assessment of trace elements (usually heavy metals) from Pakistan; most of them are epidemiological cross sectional surveys. In this current review we tried to develop a data base of HBM studies of trace elements namely arsenic, cadmium, copper, chromium, iron, lead, manganese, nickel, and zinc in biological fluids (blood, urine) and tissues (hair, nails) in general population of Pakistan. Studies from all available sources have been explored, discussed and presented in the form of tables and figures. The results of these studies were critically compared with large scale HBM programs of other countries, (US & European communities etc). It was observed from the present study that the most of the toxic metals in biological fluids/tissues in general population of Pakistan, have higher background values comparatively. For example the mean values of toxic metals like As, Cd, Cr, Ni, and Pb in blood of general population were found as 2.08 μg/L, 4.24 μg/L, 60.5 μg/L, 1.95 μg/L, 198 μg/L respectively. Similarly, the urine mean values of 67.6 μg/L, 3.2 μg/L, 16.4 μg/L, 6.2 μg/L and 86.5 μg/L were observed for As, Cd, Cr, Ni, and Pb respectively. •Human Biomonitoring of trace elements.•Current picture of the trace elements biomonitoring/cross sectional surveys in Pakistan.•Comparison of available data with other international Human biomonitoring programs.•Heavy metals are found mostly higher in blood, urine, hair and nails than most of the countries.